AUTOMATED ELECTRICAL PROTECTION SYSTEM (Auto-EProS) - Abd Azzis, Ahmad Zakwan Hariz Bin (Universiti Teknologi PETRONAS, 2012)
Power outage is a common problem happened when there are electrical faults occurred, which would lead to discontinuity of electric supply to domestic building. For domestic consumers, power continuity is very important since some of their appliances such as refrigerator, aquarium and alarm system need a continuous electric supply. However, fault occurred in the system will trip the earth leakage circuit breaker (ELCB) and disrupt the supply to all the appliances. Fault may occur due to short circuit, ground fault or overloading. Therefore, fault location detection is essential to ensure power continuity and reliability in which the fault may be isolated from the system once detected. An automatic system for fault detection and ELCB reset setting crucial to be developed to encounter the problem.